2013
DOI: 10.1108/14678041311316112
|View full text |Cite
|
Sign up to set email alerts
|

Library usage and demographic characteristics of undergraduate students in a UK university

Abstract: Library usage and demographic characteristics of undergraduate students in a UK university IntroductionIn 2011, the Library Impact Data Project presented its initial findings to the 9th Northumbria international conference on performance measurement in libraries and information services . This work demonstrated that there is a statistically significant relationship across a number of universities between library activity data and student attainment. Since then the project has received further funding from Jisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 21 publications
3
30
0
Order By: Relevance
“…This corresponds with other research that has also found males to be overrepresented in terms of physical library use as compared to their percentage of the student population. 22 Most questionnaire respondents were under the age of 25 and had been studying at the institution for two years or less (data not shown). This reflects the preponderance of two-year diploma and university programs at the institutions examined.…”
Section: Practical Limitationsmentioning
confidence: 98%
“…This corresponds with other research that has also found males to be overrepresented in terms of physical library use as compared to their percentage of the student population. 22 Most questionnaire respondents were under the age of 25 and had been studying at the institution for two years or less (data not shown). This reflects the preponderance of two-year diploma and university programs at the institutions examined.…”
Section: Practical Limitationsmentioning
confidence: 98%
“…Some of these studies have begun to incorporate other variables into their work such as the demographic characteristics of library users (Stone and Collins, 2013). Other studies have looked specifically at usage by discipline.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the library sector, research by the Library Impact Data Project found that mature students (i.e. students aged 21 and over) tend to have higher online library resource usage (Stone and Collins, 2013). However work at Wollongong (Cox and Jantti, 2012) suggests that older students do not benefit from increased library use.…”
Section: Discussionmentioning
confidence: 99%